BRSMG Madrepérola: common bean cultivar with late-darkening Carioca grain - Carneiro, José Eustáquio de Souza (2012)
The cultivar BRSMG Madrepérola, recommended for cultivation in Minas Gerais, has the feature of maintaining a light grain color for a longer period than other Carioca grain cultivars. The yield potential is high and the resistance level good to the major anthracnose races in the region.